Automatic word stress marking and syllabification for Catalan TTS - Rustullet, S.; Daniela Braga; Dias, J. (Interspeech 2008, 2008)
In this paper, a rule-based automatic syllabifier for Danish is described using the Maximal Onset Principle. Prior success rates of rule-based methods applied to Portuguese and Catalan syllabification modules were on the basis of this work. The system was implemented and tested using a very small set of rules. The results gave rise to 96.9% and 98.7% of word accuracy rate, contrary to our initial expectations, being Danish a language with a complex syllabic structure and thus difficult to be rule-driven. Comparison with data-driven syllabification system using artificial neural networks showed a higher accuracy rate of the former system. Index Terms: automatic syllabification, rule-based techniques, artificial neural networks, text-to-speech. Index Terms: Catalan text-to-speech, stress, orthographic and phonologic syllabification, prosody